Il «Fenix»: un progetto nella scuola dell'infanzia e primaria per contrastare gli effetti della deprivazione socio-culturale - Cristina Coggi; Paola Ricchiardi (LED Edizioni Universitarie, 2010)
«Fenix»: A Preschool and Primary School Project to Fight the Effects of Socio-Cultural Deprivation Many studies have shown the spreading of serious learning difficulties in socio-culturally disadvantaged children and the effects of those on their personal and social development. Expecially in the developing countries, this phenomenon is generalized and the school by itself can hardly encourage the resilience of the most underprivileged ones. In our contexts educational issues, more circumscribed, have taken different new forms, mainly related to the effects of emigration and the impacts of economic recession. In both situations, international research stresses the need to act as quickly as possible to prevent student failure, which can affect cognitive development, learning motivation and performance expectations, and lead to long-term effects of social exclusion. Starting from early schooling, action must be taken in order to work on the powerful resilience factors such as cognitive processes and the socio-affective variables favoring success. The present study illustrates a project («Fenix») started experimentally in Brazil, Salvador and in the Italian region of Piedmont. It is a complex action aimed at enhancing learning strategies, developing basic skills necessary to carry on in education, and promoting self-confidence in children's own possibilities of success, through a game-like approach to learning. The project uses concrete play materials in preschools and in the primary schools mainly digital games, focused on basic subjects like mathematics and language as well as cognitive processes.